Elucidating the potential of EGFR mutated NSCLC and identifying its multitargeted inhibitors - Anakha D. Rajeeve; Ramasamy Yamuna; P. K. Krishnan Namboori (Scientific Reports)
Abstract Lung cancer is the leading cause of cancer-related fatalities globally, accounting for the highest mortality rate among both men and women. Mutations in the epidermal growth factor receptor (EGFR) gene are frequently found in non-small cell lung cancer (NSCLC). Since curcumin and CB[2]UN support various medicinal applications in drug delivery and design, we investigated the effect of curcumin and CB[2]UN-based drugs in controlling EGFR-mutant NSCLC through a dodecagonal computational approach. Molecular docking studies revealed that the ligands curcumin (-6.9 kcal/mol) and CB[2]UN (-8.1 kcal/mol) bound more strongly to the EGFR-mutant NSCLC proteins with 2ITX and 2ITV, respectively. Molecular dynamics simulation (50 ns) investigation of protein-ligand complexes using RMSD, RMSF, Rg, and SASA indicated that curcumin and CB[2]UN with EGFR-mutant proteins are kinetically stable. In addition, MMPBSA/MMGBSA analysis confirmed the thermodynamic stability of each curcumin and CB[2]UN protein-ligand complex. Finally, KDeep absolute binding affinity calculations show energies of -6.13 kcal/mol and − 5.26 kcal/mol for 2ITX-CUR and 2ITV-CB[2]UN protein-ligand complexes, respectively. Thus, our dodecagonal strategy reveals that 2ITX-CUR and 2ITV-CB[2]UN are more likely to form protein-ligand complexes with more significant binding affinities and excellent stability throughout the 50 ns simulation time.